Comparison of Tongue Acupuncture and Traditional Acupuncture in the Treatment of Poststroke Dysarthria: A Meta-Analysis and Tongue Acupuncture System Classification Evaluation. (1st November 2022) - Yang, Xinming; Shi, Lei; Ran, Dawei; Kong, Ying; Shi, Weiping; Zhou, Jiaxiao; Gao, Huasong; Han, Yutong; Zhang, Huixue
Abstract : Objective. To discuss whether tongue acupuncture is more effective than traditional acupuncture in the treatment of poststroke dysarthria and explore the advantage of tongue acupuncture treatment parameters. Methods . We evaluated the efficacy of tongue acupuncture compared with traditional acupuncture through a rigorous meta-analysis process. The included studies were from eight databases in English and Chinese. The Cochrane risk of bias assessment tool was used to evaluate the quality of studies. Stata15.1 software was used for meta-analysis and sensitivity analysis. Tongue acupuncture therapeutic parameters were classified and counted based on tongue acupoint location, acupuncture manipulation, and the number of manipulations. Subgroup analysis was used to compare the differences between various treatment parameters. Outcome The meta-analysis eventually included a total of 9 studies. Tongue acupuncture is superior to traditional acupuncture in clinical efficacy [OR = 3.62, 95%Cl (2.24, 5.85), P < 0.0001 ], FDA score [SMD = −1.99, 95%Cl (−3.77, −0.21), P = 0.028 ], and NIHSS score [WMD = 0.86, 95%Cl (0.15, 1.57), P = 0.017, I2 = 31.7%] in the treatment of poststroke dysarthria. According to the classified statistics of tongue acupuncture treatment parameters, there are three kinds of tongue acupuncture points in 9 studies: lingual surface, sublingual, and both lingual surface and sublingual acupoints. The operation methods include the oblique stabbing of the root of the tongue, twisting after stabbing, and acupoint pricking. The number of operation methods varies from 1 to 3. Conclusion. Tongue acupuncture outperforms traditional acupuncture in terms of clinical efficacy, FDA score, and NIHSS score in the treatment of poststroke dysarthria. The curative effect of sublingual acupoints is better than that of lingual surface acupoints, the combined use of multiple manipulations is better than that of a single manipulation, and acupuncture manipulation has a cumulative effect. PROSPERO registration number: CRD42021285722.